Design of sprinkler system for fire protection installation using fully hydraulic calculation by computer aided programming method / Mohd Noor Hashim - Hashim, Mohd Noor (2002)
This final project report describe the development of the suitable Computer Application Aided program used to Design Fully Hydraulic Calculation Method for Automatic Sprinkler Installation System. In order to make the design become more practical, a possible software development tools will be used. The selection of the software should be extremely effective, flexibility, easy to handle, finally it will generate the result in fully compliance performance and in extractive graphically cosmetic outlook. To be noted that this development software application program support by the information data from the real standard code of practice including of the requirement by Loss Prevention Counsel (LPC), British Standard Institution (BSI), Uniform Building By Laws (UBBL) and Jabatan Bomba Dan Penyelamat Malaysia (JBPM) and together by relevant supporting drawing. In term of successful designing sprinkler system by using the fully hydraulic Calculation method the basic consideration are the important criteria in term to fulfill the requirement like the nature of the work, classify of occupancies according to fire hazard, pipe work sizing, water storage, type of sprinkler used and type of sprinkler head.